Utilization of Catfish Pond Wastewater for Liquid Organic Fertilizer Production in Mangir Village, Banyuwangi Regency - Widakdo, Danang Sudarso Widya Prakoso Joyo; Rusti, Nanda; Amaniyah, Maghfirotul; Halil, Halil; Hidayatulloh, Arif; Ervanda, Adinda Alya (IMPOWERMENT SOCIETY, 2026)
Catfish pond wastewater, rich in essential nutrients such as nitrogen, phosphorus, and potassium, holds significant potential as a primary raw material for liquid organic fertilizer. In Mangir Village, Banyuwangi, this waste is not utilized optimally and is often discharged directly into the environment, causing pollution. This community service activity aimed to empower the Mangir Village Farmers Group through participatory training on converting catfish pond wastewater into environmentally friendly, economically valuable liquid organic fertilizer. The methods implemented included a participatory approach through socialization, technical training in fermentation processes, practical mentoring, and assistance with marketing strategy. The results demonstrated a significant increase in farmers' knowledge and skills in processing waste into high-quality liquid fertilizer. Furthermore, there was a noticeable rise in the group's interest in adopting organic farming practices. This initiative successfully produced a marketable liquid organic fertiliser, contributing to sustainable waste management, reducing environmental pollution, and decreasing farmers' dependence on chemical fertilisers. The activity also introduced the community to the concept of a circular economy, turning waste into a valuable resource. This empowerment model can serve as a reference for other regions seeking to develop sustainable, economically productive agricultural practices.